Expectancy Theory Predictions of Salesmen's Performance - Oliver, Richard L. (Journal of Marketing Research, 1974)
As a result of a lack of empirical investigation, the variance in salesmen's performance attributable to motivational constructs has not been estimated. Vroomian expectancy theory was used to show that the motivational perceptions attributed to a set of sales “incentives” by a sample of life insurance salesmen were related to two performance criteria.